2006
DOI: 10.1359/jbmr.06s202
|View full text |Cite
|
Sign up to set email alerts
|

Is the Prevalence of Paget's Disease of Bone Decreasing?

Abstract: Secular trends in the severity and prevalence of Paget's disease over a 30-year period are described. Paget's disease has become less prevalent and patients are presenting later, with less severe disease than previously. These data suggest that environmental factors are important in the etiology of Paget's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…The prevalence of Paget disease seems to be decreasing in recent decades. 36 Paget disease is rarely diagnosed in patients younger than 40 years. In one retrospective study, younger patients were found to be more likely to present with disease in the distal appendicular skeleton and were more likely to be African American.…”
Section: Paget Disease Clinical Featuresmentioning
confidence: 99%
“…The prevalence of Paget disease seems to be decreasing in recent decades. 36 Paget disease is rarely diagnosed in patients younger than 40 years. In one retrospective study, younger patients were found to be more likely to present with disease in the distal appendicular skeleton and were more likely to be African American.…”
Section: Paget Disease Clinical Featuresmentioning
confidence: 99%
“…In Asia and Africa, in contrast, PD is very uncommon. Recent studies have suggested a decrease over time, in the prevalence of PD with less severe disease but older age at presentation [13][14][15].…”
Section: Epidemiology Of Paget's Disease (Pd)mentioning
confidence: 99%
“…Currently both SQSTM1 somatic mutations (65) as well as somatic deletions of the chromosome 18 region close to the gene encoding RANK have been reported (66;67). Another intriguing observation is the decreasing prevalence and severity of the disease seen in several populations (68). Definitely this cannot be explained by changing genetic factors as the allelic frequency of genetic variants can, at a maximum, change only very slowly over many generations.…”
Section: Missing Links and Future Perspectivesmentioning
confidence: 99%